Explicitation in the translation of QurÊ¾Änic binomials: A descriptive study - Ghuzayyil Mohammed Al-Otaibi (Indonesian Journal of Applied Linguistics, 2023)
Binomials, as a sub-type of collocation, are made of two connected words (e.g., heaven and earth). Similar to other lexical collocations, binomials can be idiomatic, ambiguous, or culture-specific. More importantly, binomials are found more commonly in religious texts such as the Holy QurÊ¾Än. However, binomials used in the Holy QurÊ¾Än are in general under-researched. Hence, using the parallel corpus (i.e., the Quranic Arabic Corpus) of the Holy QurÊ¾Än, which includes the original Arabic text (i.e., sÅ«rahs 'chapters') and seven translations by Sahih International and those by Pickthall, Yusuf Ali, Shakir, Muhammad Sarwar, Hilali-Khan, and Arberry, this study focuses on explicating shifts employed by seven translators in their translations of 120 QurÊ¾Änic binomials. Therefore, the study is descriptive in the form of a textual analysis. The results indicate that less than half of the translations were explicated compared to less than a quarter being normalized (i.e., with maintained collocability). Explicating shifts were mainly undertaken by Hilali-Khan, Yusuf Ali, and Sarwar. However, Sahih and Arberry used only a few explicating shifts. Additionally, explicating shifts basically involve those of explicative paraphrasing, complete and partial rank shifts, clitic or affix explicitation, and repetition. As noted by in this study, translating scriptures literally may result in optional explicating shifts that are mainly redundant. Hence, redundant explicitation shifts should be avoided as they may sometimes hinder processability.Â Â